Novel rubber functional composition for bicycle tire production
By using modified carbon fibers and other optimized ingredients in bicycle tire rubber compositions, the shortcomings of existing rubber compositions in wear and rolling resistance are solved, and higher wear and lower rolling resistance are achieved, extending the service life of the tire and improving riding efficiency.
Patent Information
- Application Number
- CN202411900553.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-11
AI Technical Summary
The existing bicycle tire rubber compositions have insufficient wear resistance during long-distance riding or complex road conditions, and have high rolling resistance, which affects service life and cycling efficiency.
A new type of rubber functional composition is adopted, including oil-filled polystyrene butadiene rubber, oil-filled polystyrene butadiene rubber, natural rubber, and magnesium rubber as matrix rubber, white carbon black, modified carbon fiber, carbon black, anti-slip resin and aromatic oil as filling systems, and anti-aging agents and other additives as auxiliary components. The bonding strength and dispersion properties of the carbon fiber to the rubber matrix are enhanced by the preparation process of modified carbon fiber, including surface cleaning, silanization and graft modification.
The wear resistance of the rubber composition is significantly improved and the rolling resistance is reduced, the service life of the tire is extended, the riding efficiency is improved, and the mechanical properties of the tire are enhanced.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber production, and in particular relates to a novel rubber functional composition for producing bicycle tires. Background Art
[0002] With the popularity of cycling and people's increasing requirements for riding experience, the performance of bicycle tires has become a key research area. The traditional bicycle tire rubber composition is mainly composed of rubber matrix, filler, antioxidant and other components.
[0003] In terms of rubber matrix, natural rubber and styrene-butadiene rubber are commonly used, which provide basic elasticity and toughness for tires, allowing them to adapt to different road conditions and maintain stable shape. Fillers such as carbon black have been widely used in the past. Carbon black can enhance the strength and wear resistance of rubber. Through interaction with rubber molecular chains, it effectively improves the mechanical properties of the rubber composition and prolongs the service life of the tire to a certain extent. Anti-aging agents are mainly used to prevent aging of rubber caused by ultraviolet rays, oxygen and other factors during long-term use, ensuring that the tire maintains its performance for a long time.
[0004] However, with the development of science and technology and the diversification of riding scenarios, existing rubber compositions have gradually exposed some limitations. In daily riding, especially long-distance riding or under complex road conditions, the wear resistance of tires faces severe tests. Frequent friction will cause rapid wear of rubber, which not only affects the service life of the tire, but also may bring safety hazards. At the same time, rolling resistance is also an issue that cannot be ignored. Higher rolling resistance will increase the rider's physical exertion and reduce riding efficiency, which is extremely disadvantageous for enthusiasts who pursue speed and long-distance riding.
[0005] Therefore, in order to meet the higher performance requirements of modern bicycle tires, further improving the wear resistance of the rubber composition and reducing the rolling resistance have become technical problems that need to be solved urgently. Summary of the invention
[0006] The object of the present invention is to provide a novel rubber functional composition for producing bicycle tires, aiming to improve the wear resistance of the rubber composition and reduce the rolling resistance.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A tread rubber composition for producing bicycle tires, comprising the following raw materials in parts by weight:
[0009] Base rubber: 25-30 parts of oil-extended solution-polymerized styrene-butadiene rubber, 75-120 parts of oil-extended emulsion-polymerized styrene-butadiene rubber, 10-25 parts of natural rubber, 5-15 parts of butadiene rubber;
[0010] Filling system: 45-65 parts of white carbon black, 15-30 parts of modified carbon fiber, 10-25 parts of carbon black, 3-5 parts of uniform resin, 20-25 parts of anti-slip resin, and 22-30 parts of aromatic oil;
[0011] Anti-aging system: 5-10 parts of antioxidant;
[0012] Other additives: 8-10 parts of active agent, 3-5 parts of sulfur, 4-5 parts of accelerator.
[0013] Furthermore, the tread rubber composition for producing bicycle tires comprises the following raw materials in parts by weight:
[0014] Base rubber: 27 parts of oil-extended solution-polymerized styrene-butadiene rubber, 100 parts of oil-extended emulsion-polymerized styrene-butadiene rubber, 15 parts of natural rubber, and 10 parts of butadiene rubber;
[0015] Filling system: 55 parts of white carbon black, 25 parts of modified carbon fiber, 15 parts of carbon black, 3 parts of uniform resin, 22 parts of anti-slip resin, and 22 parts of aromatic oil;
[0016] Anti-aging system: 7 parts of antioxidant;
[0017] Other additives: 8 parts of active agent, 4 parts of sulfur, and 4 parts of accelerator.
[0018] Furthermore, the modified carbon fiber is prepared by the following steps:
[0019] S1. Add carbon fiber to acetone and mix ultrasonically for 0.5 to 1 h. After the ultrasonication is completed, the system temperature is raised to 70 to 72 ° C. and refluxed at a constant temperature for 24 h. After the reflux is completed, filter to obtain defatted carbon fiber. The defatted carbon fiber is placed in a mixed acid solution. After the addition is completed, the system is heated to 90 to 100 ° C. and acidified at a constant temperature for 2 to 3 h. After the acidification is completed, filter to obtain acidified carbon fiber. The acidified carbon fiber is placed in deionized water and anhydrous ethanol for oscillation washing successively until the pH of the solution is neutral, and then placed in a constant temperature drying oven at 50 to 60 ° C. and dried to constant weight to obtain pretreated carbon fiber;
[0020] S2, adding the pretreated carbon fiber to the silane coupling agent solution with stirring, after the addition is completed, magnetic stirring is performed for 0.5 to 1 hour, and then ultrasonic stirring is performed for 0.5 to 1 hour. After completion, a suspension is obtained, and then the suspension is placed in an oil bath environment, heated to 78 to 80° C., stirred and refluxed for 4 to 5 hours, and after completion, centrifuged while hot, the upper clear liquid is removed, and the lower solid component is placed in deionized water and anhydrous ethanol for shaking washing, after washing is completed, filtered, the solid component is collected and placed in a constant temperature drying oven at 50 to 60° C. to dry to constant weight, to obtain silanized carbon fiber;
[0021] S3. Stir graphene oxide and silanized carbon fiber into N,N-dimethylformamide. After the addition is completed, stir magnetically for 0.5-1h, and then stir ultrasonically for 0.5-1h to obtain a suspension. Then place the suspension in an oil bath environment, heat it to 100-110°C, stir and reflux for 5-6h. After completion, centrifuge while hot to remove the upper clear liquid, and place the lower solid component in deionized water and anhydrous ethanol for shaking washing. After washing, filter, collect the solid components and place them in a constant temperature drying oven at 50-60°C for drying for 24h to obtain modified carbon fiber.
[0022] Furthermore, the dosage ratio of acetone and carbon fiber in S1 is 20-50 mL: 1 g; the mixed acid solution is prepared by mixing 68 wt % concentrated nitric acid and 98 wt % concentrated sulfuric acid in a volume ratio of 1:1; the dosage ratio of the defatted carbon fiber and the mixed acid solution is 1 g: 40-50 mL.
[0023] Furthermore, the dosage ratio of the silane coupling agent solution and the pretreated carbon fiber in S2 is 100 mL: 3-5 g.
[0024] Furthermore, the silane coupling agent solution in S2 is prepared by the following steps: anhydrous ethanol and deionized water are mixed in a volume ratio of 9:1 to obtain an ethanol solution, and then KH-550 is added to the ethanol solution in a volume ratio of 4 to 5:1, and stirred at room temperature for 1 to 2 hours. After stirring, a silane coupling agent solution is obtained.
[0025] Furthermore, the usage ratio of N,N-dimethylformamide, graphene oxide and silylated carbon fiber in S3 is 200mL:0.1-0.5g:1g.
[0026] Furthermore, the grade of the carbon black is N330; and the activator is zinc oxide.
[0027] Furthermore, the mesh size of the sulfur is 200 meshes.
[0028] Furthermore, the preparation method of the novel rubber functional composition comprises the following steps:
[0029] S1. Weigh the raw materials oil-extended solution-polymerized butadiene styrene rubber, oil-extended emulsion-polymerized butadiene styrene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant, activator, carbon black, aromatic oil, sulfur and accelerator according to mass parts and set aside;
[0030] S2, the oil-extended solution-polymerized styrene-butadiene rubber, the oil-extended emulsion-polymerized styrene-butadiene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant and activator are mixed and put into an internal mixer for mixing, the speed of the internal mixer is set to 35-50r / min, the mixing time is 15-50s, and after the mixing is completed, a primary mixed material is obtained;
[0031] S3, after the internal mixer is lifted, the raw material modified carbon fiber, carbon black and 70% to 80% of the total mass of aromatic oil are added to the primary mixed material, and the speed is set to 20 to 45 r / min, and the mixed material is mixed until the temperature reaches 100 to 125°C to obtain a secondary mixed material, and then the plug is lifted, and the remaining aromatic oil is added to the secondary mixed material, and the speed is set to 10 to 25 r / min, and the mixed material is mixed until the temperature reaches 135 to 150°C, and the temperature is kept constant for 1 to 2 minutes. After the mixing is completed, the material is unloaded to obtain a masterbatch;
[0032] S4. Mix the masterbatch, raw sulfur and accelerator and put them into an internal mixer. Set the speed to 15-40 r / min and mix until the temperature reaches 80-100° C. The mixing time is 10-30 s. After the mixing is completed, unload the material and cool it to room temperature to obtain a tread rubber composition.
[0033] Beneficial effects of the present invention:
[0034] The present invention provides a tread rubber composition for producing bicycle tires. The present invention improves the components and proportions of the rubber composition to ensure that the rubber composition has excellent mechanical properties and hardness. At the same time, the prepared rubber composition has both high wear resistance and low rolling resistance. The specific principle is as follows:
[0035] First, the tread rubber composition of the present invention is added with the self-made modified carbon fiber of the present invention. The carbon fiber itself has the characteristics of high strength, but due to the characteristics of the smooth surface, the wettability and adsorption between the carbon fiber and the rubber matrix are poor, and the interface bonding strength between the carbon fiber and the rubber matrix is weak. Therefore, the present invention modifies the carbon fiber. In the process of preparing the modified carbon fiber, the present invention successively performs surface cleaning and activation (pretreatment), silanization treatment and grafting modification treatment on the carbon fiber. First, in the process of pretreatment of the carbon fiber, acetone is used to remove the resin layer covering the surface of the carbon fiber. This step reduces the impurities on the surface of the carbon fiber and exposes more active sites, which is beneficial to the subsequent modification treatment; then, the degreased carbon fiber is acidified by a mixed acid solution, and hydroxyl and carboxyl groups are introduced on the surface of the carbon fiber. The introduction of these functional groups enhances the bonding strength between the carbon fiber and the rubber matrix. In the rubber composition, the hydroxyl and carboxyl groups can form hydrogen bonds with the rubber molecules for bonding, so that the carbon fiber is better dispersed in the rubber matrix and can effectively transmit stress, thereby improving the wear resistance of the rubber composition. Then, during the silanization treatment process, the silane coupling agent (KH-550) can play a bridging role between the carbon fiber and the rubber. This bridging role makes the interface bonding between the carbon fiber and the rubber tighter. During the rolling process of the tire, it can effectively prevent the carbon fiber from falling off from the rubber matrix. The tight interface bonding helps to reduce the energy loss caused by interface friction, thereby reducing the rolling resistance of the rubber composition; finally, the present invention uses silane as a bridge to graft graphene oxide on the surface of the carbon fiber. Specifically, after the carbon fiber is oxidized by a strong acid, the silane coupling agent is used to react with the carboxyl and hydroxyl groups on its surface to achieve silanization functionalization treatment of the carbon fiber. The terminal amino group of the silane coupling agent then undergoes an amidation reaction with the carboxyl group of the graphene oxide to form an amide bond, thereby achieving the purpose of grafting graphene oxide on the surface of the carbon fiber. The purpose of grafting graphene oxide is: first, graphene oxide can fill The graphene oxide is filled between the carbon fibers and in the gaps between the carbon fibers and the rubber matrix to form a denser network structure. When the tire is subjected to friction, the network structure can effectively resist wear and improve the wear resistance of the rubber composition. Then, the present invention uses chemical grafting to form a chemical bond with a relatively strong bond energy between the carbon fibers and the graphene, rather than the van der Waals force formed by other methods, thereby increasing the interaction between the two and effectively improving the pull-out resistance of the interface between the graphene oxide and the carbon fibers. The graphene itself also has excellent friction reduction (friction reduction) and mechanical properties (rigidity and strength). The synergistic effect of the graphene oxide and the carbon fibers can reduce the friction between the rubber molecular chains, and also help to reduce the rolling resistance of the rubber composition, and further enhance the mechanical properties of the rubber composition, so that the tire deforms less during rolling, reducing the energy loss caused by repeated deformation, thereby reducing the rolling resistance.
[0036] Then, the tread rubber composition of the present invention is added with anti-skid resin and aromatic oil, wherein the anti-skid resin is used to improve the anti-skid performance of the rubber composition and also helps to enhance the mechanical properties of the rubber composition; the aromatic oil helps to improve the grip of the tire tread under different road conditions, especially under wet conditions, the aromatic oil can improve the contact between the tire and the road and improve the anti-skid performance.
[0037] Finally, the tread rubber composition of the present invention is added with active agents zinc oxide, sulfur and an accelerator, wherein zinc oxide is used as an active agent to promote the vulcanization reaction of the rubber. During the vulcanization process, zinc oxide interacts with sulfur to form zinc sulfide, and zinc sulfide undergoes a cross-linking reaction with the rubber molecular chain to increase the cross-linking density of the rubber composition, thereby enhancing the tensile strength of the rubber composition; the accelerator is used to accelerate the vulcanization reaction of sulfur, and the accelerator can make the vulcanization reaction proceed more uniformly and rapidly, thereby increasing the cross-linking density of the rubber composition and enhancing the mechanical properties of the rubber composition. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] Preparation of modified carbon fiber:
[0041] Carbon fiber pretreatment: Take a three-necked flask, add acetone (AR; ≥99.5%; purchased from Sinopharm Chemical Reagent Co., Ltd.), then add carbon fiber (diameter 7 μm, purchased from Zhongli New Materials Co., Ltd.) to the acetone, wherein the amount ratio of acetone to carbon fiber is 20 mL: 1 g, ultrasonic mixing is performed for 0.5 h, after the ultrasonication is completed, the system temperature is raised to 70 ° C, constant temperature reflux is performed for 24 h, and the resin layer covering the surface of the carbon fiber is removed by acetone. After the reflux is completed, filter to obtain defatted carbon fiber, and place the defatted carbon fiber in a mixed acid solution, wherein the mixed acid solution is composed of 68 wt% concentrated Nitric acid (self-prepared) and 98wt% concentrated sulfuric acid (self-prepared) are mixed in a volume ratio of 1:1. The amount ratio of defatted carbon fiber and mixed acid solution is 1g:40mL. After the addition is completed, the system is heated to 90°C and acidified at a constant temperature for 2h. The acidification process introduces hydroxyl and carboxyl groups to the surface of the defatted carbon fiber to achieve the subsequent grafting modification process. After the acidification is completed, it is filtered to obtain acidified carbon fiber. The acidified carbon fiber is placed in deionized water and anhydrous ethanol for oscillation washing in turn until the pH of the solution is neutral, and then placed in a 50°C constant temperature drying oven to dry to constant weight to obtain pretreated carbon fiber.
[0042] Prepare a silane coupling agent solution: mix anhydrous ethanol and deionized water in a volume ratio of 9:1 to obtain an ethanol solution, then add KH-550 (99%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) in a volume ratio of 5:1 to the ethanol solution, stir at room temperature for 1 hour, and after stirring, obtain a silane coupling agent solution.
[0043] Silanization treatment: add the pretreated carbon fiber to the silane coupling agent solution with stirring, wherein the amount ratio of the silane coupling agent solution to the pretreated carbon fiber is 100mL:5g. After the addition is completed, magnetic stirring is performed for 0.5h, and then ultrasonic stirring is performed for 0.5h. After completion, a suspension is obtained, and then the suspension is placed in an oil bath environment, heated to 78°C, and stirred and refluxed for 4h. After completion, centrifugation is performed while hot to remove the upper clear liquid, and the lower solid component is placed in deionized water and anhydrous ethanol for oscillation washing in turn to remove excess silane coupling agent on the surface of the carbon fiber. After washing, it is filtered, the solid component is collected and placed in a 50°C constant temperature drying oven to dry to constant weight to obtain silanized carbon fiber.
[0044] Grafting modification: graphene oxide (model XF033; purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.) and silanized carbon fiber were added to N,N-dimethylformamide (AR; ≥99.5%; purchased from Sinopharm Chemical Reagent Co., Ltd.) with stirring, wherein the amount ratio of N,N-dimethylformamide, graphene oxide and silanized carbon fiber was 200mL:0.1g:1g. After the addition was completed, magnetic stirring was performed for 0.5h, and then ultrasonic stirring was performed for 0.5h to obtain a suspension, and then the suspension was placed in an oil bath environment, heated to 100°C, stirred and refluxed for 5h, and after completion, centrifuged while hot to remove the upper clear liquid, and the lower solid component was placed in deionized water and anhydrous ethanol for oscillation washing. After washing, it was filtered, and the solid component was collected and placed in a constant temperature drying oven at 50°C for drying for 24h to obtain modified carbon fiber.
[0045] Example 2
[0046] Preparation of modified carbon fiber:
[0047] Carbon fiber pretreatment: Take a three-necked flask, add acetone (AR; ≥99.5%; purchased from Sinopharm Chemical Reagent Co., Ltd.), then add carbon fiber (diameter 7 μm, purchased from Zhongli New Materials Co., Ltd.) to the acetone, wherein the amount ratio of acetone to carbon fiber is 40 mL: 1 g, ultrasonic mixing for 1 h, after the completion of the ultrasonication, the system temperature is raised to 70 ° C, constant temperature reflux for 24 h, and the resin layer covering the surface of the carbon fiber is removed by acetone. After the reflux is completed, filter to obtain defatted carbon fiber, and place the defatted carbon fiber in a mixed acid solution, wherein the mixed acid solution is composed of 68wt% concentrated nitric acid Acid (self-prepared) and 98wt% concentrated sulfuric acid (self-prepared) are mixed in a volume ratio of 1:1. The amount ratio of defatted carbon fiber and mixed acid solution is 1g:50mL. After the addition is completed, the system is heated to 95°C and acidified at a constant temperature for 3h. The acidification process introduces hydroxyl and carboxyl groups to the surface of the defatted carbon fiber to achieve the subsequent grafting modification process. After the acidification is completed, it is filtered to obtain acidified carbon fiber. The acidified carbon fiber is placed in deionized water and anhydrous ethanol for oscillation washing in turn, washed until the pH of the solution is neutral, and then placed in a 50°C constant temperature drying oven to dry to constant weight to obtain pretreated carbon fiber.
[0048] Prepare a silane coupling agent solution: mix anhydrous ethanol and deionized water in a volume ratio of 9:1 to obtain an ethanol solution, then add KH-550 (99%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) in a volume ratio of 4:1 to the ethanol solution, stir at room temperature for 2 hours, and after stirring, obtain a silane coupling agent solution.
[0049] Silanization treatment: add the pretreated carbon fiber to the silane coupling agent solution with stirring, wherein the amount ratio of the silane coupling agent solution to the pretreated carbon fiber is 100mL:4g. After the addition is completed, magnetic stirring is performed for 1h, and then ultrasonic stirring is performed for 1h. After completion, a suspension is obtained, and then the suspension is placed in an oil bath environment, heated to 78°C, and stirred and refluxed for 5h. After completion, centrifugation is performed while hot to remove the upper clear liquid, and the lower solid component is placed in deionized water and anhydrous ethanol for oscillation washing in turn to remove excess silane coupling agent on the surface of the carbon fiber. After washing, it is filtered, the solid component is collected and placed in a 50°C constant temperature drying oven to dry to constant weight to obtain silanized carbon fiber.
[0050] Grafting modification: graphene oxide (model XF033; purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.) and silanized carbon fiber were added to N,N-dimethylformamide (AR; ≥99.5%; purchased from Sinopharm Chemical Reagent Co., Ltd.) with stirring, wherein the amount ratio of N,N-dimethylformamide, graphene oxide and silanized carbon fiber was 200mL:0.45g:1g. After the addition was completed, magnetic stirring was performed for 1h, and then ultrasonic stirring was performed for 1h to obtain a suspension. The suspension was then placed in an oil bath environment, heated to 105°C, stirred and refluxed for 6h, and after completion, centrifuged while hot to remove the upper clear liquid, and the lower solid components were placed in deionized water and anhydrous ethanol for oscillation washing. After washing, they were filtered, and the solid components were collected and placed in a 55°C constant temperature drying oven for drying for 24h to obtain modified carbon fiber.
[0051] Example 3
[0052] Preparation of modified carbon fiber:
[0053] Carbon fiber pretreatment: Take a three-necked flask, add acetone (AR; ≥99.5%; purchased from Sinopharm Chemical Reagent Co., Ltd.), then add carbon fiber (diameter 7 μm, purchased from Zhongli New Materials Co., Ltd.) to the acetone, wherein the amount ratio of acetone to carbon fiber is 50 mL: 1 g, ultrasonic mixing for 1 h, after the completion of the ultrasonication, the system temperature is raised to 72 ° C, constant temperature reflux for 24 h, and the resin layer covering the surface of the carbon fiber is removed by acetone. After the reflux is completed, filter to obtain defatted carbon fiber, and place the defatted carbon fiber in a mixed acid solution, wherein the mixed acid solution is composed of 68wt% concentrated nitric acid. Acid (self-prepared) and 98wt% concentrated sulfuric acid (self-prepared) are mixed in a volume ratio of 1:1. The amount ratio of defatted carbon fiber and mixed acid solution is 1g:50mL. After the addition is completed, the system is heated to 100°C and acidified at a constant temperature for 3h. The acidification process introduces hydroxyl and carboxyl groups to the surface of the defatted carbon fiber to achieve the subsequent grafting modification process. After the acidification is completed, it is filtered to obtain acidified carbon fiber. The acidified carbon fiber is placed in deionized water and anhydrous ethanol for oscillation washing in turn, washed until the pH of the solution is neutral, and then placed in a 60°C constant temperature drying oven to dry to constant weight to obtain pretreated carbon fiber.
[0054] Prepare a silane coupling agent solution: mix anhydrous ethanol and deionized water in a volume ratio of 9:1 to obtain an ethanol solution, then add KH-550 (99%; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) in a volume ratio of 4:1 to the ethanol solution, stir at room temperature for 2 hours, and after stirring, obtain a silane coupling agent solution.
[0055] Silanization treatment: add the pretreated carbon fiber to the silane coupling agent solution with stirring, wherein the amount ratio of the silane coupling agent solution to the pretreated carbon fiber is 100mL:3g. After the addition is completed, magnetic stirring is performed for 1h, and then ultrasonic stirring is performed for 1h. After completion, a suspension is obtained, and then the suspension is placed in an oil bath environment, heated to 80°C, and stirred and refluxed for 5h. After completion, centrifugation is performed while hot to remove the upper clear liquid, and the lower solid component is placed in deionized water and anhydrous ethanol for oscillation washing in turn to remove excess silane coupling agent on the surface of the carbon fiber. After washing, it is filtered, the solid component is collected, and placed in a 60°C constant temperature drying oven to dry to constant weight to obtain silanized carbon fiber.
[0056] Graft modification: graphene oxide (model XF033; purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.) and silanized carbon fiber were added to N,N-dimethylformamide (AR; ≥99.5%; purchased from Sinopharm Chemical Reagent Co., Ltd.) with stirring, wherein the amount ratio of N,N-dimethylformamide, graphene oxide and silanized carbon fiber was 200mL:0.5g:1g. After the addition was completed, magnetic stirring was performed for 1h, and then ultrasonic stirring was performed for 1h to obtain a suspension. The suspension was then placed in an oil bath environment, heated to 110°C, and stirred and refluxed for 6h. After completion, centrifugation was performed while hot to remove the upper clear liquid, and the lower solid components were placed in deionized water and anhydrous ethanol for oscillation washing. After washing, filtration was performed, and the solid components were collected and placed in a constant temperature drying oven at 60°C for drying for 24h to obtain modified carbon fiber.
[0057] Example 4
[0058] Preparation of tread rubber composition for bicycle tire production:
[0059] First, the tread rubber composition includes the following raw materials in parts by weight:
[0060] Base rubber: 25 parts of oil-extended solution-polymerized styrene-butadiene rubber, 75 parts of oil-extended emulsion-polymerized styrene-butadiene rubber, 10 parts of natural rubber, and 5 parts of butadiene rubber;
[0061] Filling system: 45 parts of white carbon black, 15 parts of modified carbon fiber prepared in Example 1, 10 parts of carbon black, 3 parts of uniform resin, 20 parts of anti-slip resin, and 22 parts of aromatic oil;
[0062] Anti-aging system: 5 parts of antioxidant;
[0063] Other additives: 8 parts of active agent, 3 parts of sulfur, and 4 parts of accelerator.
[0064] Among the base rubbers, the brand of the oil-extended solution-polymerized styrene-butadiene rubber (SSBR) is 2564S, the oil-filling amount is 37.5 parts, and it is purchased from PetroChina Xinjiang Dushanzi Petrochemical Co., Ltd.; the brand of the oil-extended emulsion-polymerized styrene-butadiene rubber (ESBR) is 1712, the oil-filling amount is 28.5 parts, and it is purchased from PetroChina Lanzhou Petrochemical Co., Ltd.; the model of the natural rubber is SCR WF, purchased from Xishuangbanna Manlie Rubber Co., Ltd.; the brand of the butadiene rubber is BR9000, purchased from PetroChina Yangzi Petrochemical Co., Ltd.
[0065] In the filling system, white carbon black was purchased from Sinopharm Chemical Reagent Co., Ltd.; among them, the brand of carbon black was N330, purchased from Black Cat Carbon Black Co., Ltd.; the brand of uniform resin was 145A, purchased from Shanghai Heshan Materials Technology Co., Ltd.; the brand of anti-slip resin was Impera 1504, purchased from Eastman Company of the United States; and aromatic oil was purchased from Dongying Mantec Petrochemical Co., Ltd.
[0066] In the anti-aging system, the brand of the antioxidant is Curekind 4020, produced by Ningbo Aikemu New Materials Co., Ltd.
[0067] Among other additives, the active agent is zinc oxide (purity 99.7%), and the zinc oxide was purchased from Liuzhou Zhongse Zinc Products Co., Ltd.; among them, the mesh size of sulfur is 200 mesh, purchased from Jiangsu Sopo Chemical Co., Ltd.; among them, the brand of the accelerator is CBS, purchased from Shandong Shangshun Chemical Co., Ltd.
[0068] Then, the preparation method of the tread rubber composition comprises the following steps:
[0069] S1. Weigh the raw materials oil-extended solution-polymerized butadiene styrene rubber, oil-extended emulsion-polymerized butadiene styrene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant, activator, carbon black, aromatic oil, sulfur and accelerator according to mass parts and set aside;
[0070] S2, after mixing the oil-extended solution-polymerized styrene-butadiene rubber, the oil-extended emulsion-polymerized styrene-butadiene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant and activating agent, the mixture is put into an internal mixer for mixing, the speed of the internal mixer is set to 35r / min, the mixing time is 15s, and after mixing is completed, a primary mixed material is obtained;
[0071] S3, after the internal mixer is lifted, the modified carbon fiber prepared in Example 1, carbon black and 70% of the total mass of aromatic oil are added to the primary mixed material, and the speed is set to 20r / min, and the mixed material is mixed until the temperature reaches 100°C to obtain a secondary mixed material, and the mixer is lifted again, and the remaining aromatic oil is added to the secondary mixed material, and the speed is set to 10r / min, and the mixed material is mixed until the temperature reaches 135°C, and the mixed material is mixed at a constant temperature for 1min. After the mixing is completed, the material is unloaded to obtain a masterbatch;
[0072] S4. Mix the masterbatch, raw sulfur and accelerator and put them into an internal mixer. Set the speed to 15 r / min and mix until the temperature reaches 80° C. The mixing time is 10 s. After the mixing is completed, unload the material and cool it to room temperature to obtain a tread rubber composition.
[0073] Example 5
[0074] Preparation of tread rubber composition for bicycle tire production:
[0075] First, the tread rubber composition includes the following raw materials in parts by weight:
[0076] Base rubber: 27 parts of oil-extended solution-polymerized styrene-butadiene rubber, 100 parts of oil-extended emulsion-polymerized styrene-butadiene rubber, 15 parts of natural rubber, and 10 parts of butadiene rubber;
[0077] Filling system: 55 parts of white carbon black, 25 parts of modified carbon fiber prepared in Example 2, 15 parts of carbon black, 3 parts of uniform resin, 22 parts of anti-slip resin, and 25 parts of aromatic oil;
[0078] Anti-aging system: 7 parts of antioxidant;
[0079] Other additives: 8 parts of active agent, 4 parts of sulfur, and 4 parts of accelerator.
[0080] Among the base rubbers, the brand of the oil-extended solution-polymerized styrene-butadiene rubber (SSBR) is 2564S, the oil-filling amount is 37.5 parts, and it is purchased from PetroChina Xinjiang Dushanzi Petrochemical Co., Ltd.; the brand of the oil-extended emulsion-polymerized styrene-butadiene rubber (ESBR) is 1712, the oil-filling amount is 28.5 parts, and it is purchased from PetroChina Lanzhou Petrochemical Co., Ltd.; the model of the natural rubber is SCR WF, purchased from Xishuangbanna Manlie Rubber Co., Ltd.; the brand of the butadiene rubber is BR9000, purchased from PetroChina Yangzi Petrochemical Co., Ltd.
[0081] In the filling system, white carbon black was purchased from Sinopharm Chemical Reagent Co., Ltd.; among them, the brand of carbon black was N330, purchased from Black Cat Carbon Black Co., Ltd.; the brand of uniform resin was 145A, purchased from Shanghai Heshan Materials Technology Co., Ltd.; the brand of anti-slip resin was Impera 1504, purchased from Eastman Company of the United States; and aromatic oil was purchased from Dongying Mantec Petrochemical Co., Ltd.
[0082] In the anti-aging system, the brand of the antioxidant is Curekind 4020, produced by Ningbo Aikemu New Materials Co., Ltd.
[0083] Among other additives, the active agent is zinc oxide (purity 99.7%), and the zinc oxide was purchased from Liuzhou Zhongse Zinc Products Co., Ltd.; among them, the mesh size of sulfur is 200 mesh, purchased from Jiangsu Sopo Chemical Co., Ltd.; among them, the brand of the accelerator is CBS, purchased from Shandong Shangshun Chemical Co., Ltd.
[0084] Then, the preparation method of the tread rubber composition comprises the following steps:
[0085] S1. Weigh the raw materials oil-extended solution-polymerized butadiene styrene rubber, oil-extended emulsion-polymerized butadiene styrene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant, activator, carbon black, aromatic oil, sulfur and accelerator according to mass parts and set aside;
[0086] S2, the oil-extended solution-polymerized styrene-butadiene rubber, the oil-extended emulsion-polymerized styrene-butadiene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant and activating agent are mixed and put into an internal mixer for mixing, the speed of the internal mixer is set to 40r / min, the mixing time is 40s, and after mixing is completed, a primary mixed material is obtained;
[0087] S3, after the internal mixer is lifted, the modified carbon fiber prepared in Example 2, carbon black and 70% of the total mass of aromatic oil are added to the primary mixed material, and the speed is set to 40r / min, and the mixed material is mixed until the temperature reaches 120°C to obtain a secondary mixed material, and the mixer is lifted again, and the remaining aromatic oil is added to the secondary mixed material, and the speed is set to 20r / min, and the mixed material is mixed until the temperature reaches 140°C, and the mixed material is mixed at a constant temperature for 2min. After the mixing is completed, the material is unloaded to obtain a masterbatch;
[0088] S4. The masterbatch, the raw sulfur and the accelerator are mixed and put into an internal mixer. The speed is set to 30 r / min, and the mixing is performed until the temperature reaches 90° C. The mixing time is 30 s. After the mixing is completed, the material is unloaded and cooled to room temperature to obtain a tread rubber composition.
[0089] Example 6
[0090] Preparation of tread rubber composition for bicycle tire production:
[0091] First, the tread rubber composition includes the following raw materials in parts by weight:
[0092] Base rubber: 30 parts of oil-extended solution-polymerized styrene-butadiene rubber, 120 parts of oil-extended emulsion-polymerized styrene-butadiene rubber, 25 parts of natural rubber, and 15 parts of butadiene rubber;
[0093] Filling system: 65 parts of white carbon black, 30 parts of modified carbon fiber prepared in Example 3, 25 parts of carbon black, 5 parts of uniform resin, 25 parts of anti-slip resin, and 30 parts of aromatic oil;
[0094] Anti-aging system: 10 parts of antioxidant;
[0095] Other additives: 10 parts of activator, 5 parts of sulfur, and 5 parts of accelerator.
[0096] Among the base rubbers, the brand of the oil-extended solution-polymerized styrene-butadiene rubber (SSBR) is 2564S, the oil-filling amount is 37.5 parts, and it is purchased from PetroChina Xinjiang Dushanzi Petrochemical Co., Ltd.; the brand of the oil-extended emulsion-polymerized styrene-butadiene rubber (ESBR) is 1712, the oil-filling amount is 28.5 parts, and it is purchased from PetroChina Lanzhou Petrochemical Co., Ltd.; the model of the natural rubber is SCR WF, purchased from Xishuangbanna Manlie Rubber Co., Ltd.; the brand of the butadiene rubber is BR9000, purchased from PetroChina Yangzi Petrochemical Co., Ltd.
[0097] In the filling system, white carbon black was purchased from Sinopharm Chemical Reagent Co., Ltd.; among them, the brand of carbon black was N330, purchased from Black Cat Carbon Black Co., Ltd.; the brand of uniform resin was 145A, purchased from Shanghai Heshan Materials Technology Co., Ltd.; the brand of anti-slip resin was Impera 1504, purchased from Eastman Company of the United States; and aromatic oil was purchased from Dongying Mantec Petrochemical Co., Ltd.
[0098] In the anti-aging system, the brand of the antioxidant is Curekind 4020, produced by Ningbo Aikemu New Materials Co., Ltd.
[0099] Among other additives, the active agent is zinc oxide (purity 99.7%), and the zinc oxide was purchased from Liuzhou Zhongse Zinc Products Co., Ltd.; among them, the mesh size of sulfur is 200 mesh, purchased from Jiangsu Sopo Chemical Co., Ltd.; among them, the brand of the accelerator is CBS, purchased from Shandong Shangshun Chemical Co., Ltd.
[0100] Then, the preparation method of the tread rubber composition comprises the following steps:
[0101] S1. Weigh the raw materials oil-extended solution-polymerized butadiene styrene rubber, oil-extended emulsion-polymerized butadiene styrene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant, activator, carbon black, aromatic oil, sulfur and accelerator according to mass parts and set aside;
[0102] S2, the oil-extended solution-polymerized styrene-butadiene rubber, the oil-extended emulsion-polymerized styrene-butadiene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant and activating agent are mixed and put into an internal mixer for mixing, the speed of the internal mixer is set to 50r / min, the mixing time is 50s, and after mixing is completed, a primary mixed material is obtained;
[0103] S3, after the internal mixer is lifted, the modified carbon fiber prepared in Example 3, carbon black and 80% of the total mass of aromatic oil are added to the primary mixed material, and the speed is set to 45r / min, and the mixed material is mixed until the temperature reaches 125°C to obtain a secondary mixed material, and the mixer is lifted again, and the remaining aromatic oil is added to the secondary mixed material, and the speed is set to 25r / min, and the mixed material is mixed until the temperature reaches 150°C, and the mixed material is mixed at a constant temperature for 2min. After the mixing is completed, the material is unloaded to obtain a masterbatch;
[0104] S4. Mix the masterbatch, raw sulfur and accelerator and put them into an internal mixer. Set the speed to 40 r / min and mix until the temperature reaches 100° C. The mixing time is 30 s. After the mixing is completed, unload the material and cool it to room temperature to obtain a tread rubber composition.
[0105] Comparative Example 1
[0106] Comparative Example 1 is the control group of Example 5, in which the modified carbon fiber prepared in Example 2 in Example 5 is replaced with carbon fiber (diameter 7 μm, purchased from Zhongli New Materials Co., Ltd.), and the remaining raw materials, raw material amounts and preparation methods remain unchanged from Example 5, to finally obtain a tread rubber composition.
[0107] Comparative Example 2
[0108] Comparative Example 1 is the control group of Example 5, except that the modified carbon fiber prepared in Example 2 in Example 5 is removed, and the remaining raw materials, raw material amounts and preparation methods remain the same as in Example 5, and finally a tread rubber composition is obtained.
[0109] The performance test was performed on the rubber functional compositions prepared in Examples 4 to 6 and Comparative Examples 1 to 2. The performance test process is as follows, and the test results are shown in Table 1:
[0110] (1) Mechanical properties: The tensile strength (MPa) and elongation at break (%) of the rubber functional composition were measured according to the method in GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”.
[0111] (2) Hardness: The Shore A hardness of the rubber functional composition is measured by referring to the method in GB / T 531.1-2008 “Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore durometer method (Shore hardness)”.
[0112] (3) Wear volume: The wear volume of the rubber functional composition after driving 1.61 km was measured according to the method in GB / T 1689-2014 “Determination of wear resistance of vulcanized rubber (using Akron abrasion tester)”.
[0113] (4) Rolling resistance: The temperature of the vulcanized rubber was scanned using a DMA instrument. The test conditions were: dual cantilever mode, temperature -80 to (+80)°C, frequency 10 Hz, and heating rate 2°C / min. At a frequency of 10 Hz, tanδ (loss factor) at 0°C was used to characterize the anti-slip performance of the vulcanized rubber. The larger the value, the better the anti-slip performance of the vulcanized rubber. Tanδ at 60°C was used to characterize the rolling resistance of the vulcanized rubber. The smaller the value, the lower the rolling resistance of the vulcanized rubber.
[0114] Table 1 Test results
[0115] project Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Tensile strength / MPa 24.89 25.12 25.04 23.14 20.31 Elongation at break / % 583.22 610.87 597.91 557.60 504.28 Shore A Hardness 60 62 65 58 55 Wear volume 0.135 0.132 0.144 0.177 0.231 tanδ / 60℃ 0.080 0.074 0.075 0.104 0.121
[0116] It can be seen from Table 1 that the rubber functional compositions prepared in Examples 4 to 6 of the present invention have excellent mechanical properties and hardness, as well as excellent wear resistance and extremely low rolling resistance. Furthermore, by comparing the data of Example 5 with Comparative Examples 1 and 2, respectively, it can be obtained that adding the modified carbon fiber prepared by the present invention can significantly improve the wear resistance of the rubber composition and reduce the rolling resistance of the rubber composition.
[0117] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.
[0118] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A novel rubber functional composition for bicycle tire production, characterized in that: Including the following raw materials by weight: Base rubber: 25-30 parts of oil-extended solution-polymerized styrene-butadiene rubber, 75-120 parts of oil-extended emulsion-polymerized styrene-butadiene rubber, 10-25 parts of natural rubber, 5-15 parts of butadiene rubber; Filling system: 45-65 parts of white carbon black, 15-30 parts of modified carbon fiber, 10-25 parts of carbon black, 3-5 parts of uniform resin, 20-25 parts of anti-slip resin, and 22-30 parts of aromatic oil; Anti-aging system: 5-10 parts of antioxidant; Other additives: 8-10 parts of active agent, 3-5 parts of sulfur, 4-5 parts of accelerator.
2. The novel rubber functional composition for producing bicycle tires according to claim 1, characterized in that: Including the following raw materials by weight: Base rubber: 27 parts of oil-extended solution-polymerized styrene-butadiene rubber, 100 parts of oil-extended emulsion-polymerized styrene-butadiene rubber, 15 parts of natural rubber, and 10 parts of butadiene rubber; Filling system: 55 parts of white carbon black, 25 parts of modified carbon fiber, 15 parts of carbon black, 3 parts of uniform resin, 22 parts of anti-slip resin, and 22 parts of aromatic oil; Anti-aging system: 7 parts of antioxidant; Other additives: 8 parts of active agent, 4 parts of sulfur, and 4 parts of accelerator.
3. The novel rubber functional composition for producing bicycle tires according to claim 1, characterized in that: The modified carbon fiber is prepared by the following steps: S1. Add carbon fiber to acetone and mix ultrasonically for 0.5 to 1 h. After the ultrasonication is completed, the system temperature is raised to 70 to 72 ° C. and refluxed at a constant temperature for 24 h. After the reflux is completed, filter to obtain defatted carbon fiber. The defatted carbon fiber is placed in a mixed acid solution. After the addition is completed, the system is heated to 90 to 100 ° C. and acidified at a constant temperature for 2 to 3 h. After the acidification is completed, filter to obtain acidified carbon fiber. The acidified carbon fiber is placed in deionized water and anhydrous ethanol for oscillation washing successively until the pH of the solution is neutral, and then placed in a constant temperature drying oven at 50 to 60 ° C. and dried to constant weight to obtain pretreated carbon fiber; S2, adding the pretreated carbon fiber to the silane coupling agent solution with stirring, after the addition is completed, magnetic stirring is performed for 0.5 to 1 hour, and then ultrasonic stirring is performed for 0.5 to 1 hour. After completion, a suspension is obtained, and then the suspension is placed in an oil bath environment, heated to 78 to 80° C., stirred and refluxed for 4 to 5 hours, and after completion, centrifuged while hot, the upper clear liquid is removed, and the lower solid component is placed in deionized water and anhydrous ethanol for shaking washing, after washing is completed, filtered, the solid component is collected and placed in a constant temperature drying oven at 50 to 60° C. to dry to constant weight, to obtain silanized carbon fiber; S3. Stir graphene oxide and silanized carbon fiber into N,N-dimethylformamide. After the addition is completed, stir magnetically for 0.5-1h, and then stir ultrasonically for 0.5-1h to obtain a suspension. Then place the suspension in an oil bath environment, heat it to 100-110°C, stir and reflux for 5-6h. After completion, centrifuge while hot to remove the upper clear liquid, and place the lower solid component in deionized water and anhydrous ethanol for shaking washing. After washing, filter, collect the solid components and place them in a constant temperature drying oven at 50-60°C for drying for 24h to obtain modified carbon fiber.
4. The novel rubber functional composition for producing bicycle tires according to claim 3, characterized in that: The dosage ratio of acetone and carbon fiber in S1 is 20-50 mL: 1 g; the mixed acid solution is prepared by mixing 68 wt % concentrated nitric acid and 98 wt % concentrated sulfuric acid in a volume ratio of 1:1; the dosage ratio of the degreased carbon fiber and the mixed acid solution is 1 g: 40-50 mL.
5. The novel rubber functional composition for producing bicycle tires according to claim 3, characterized in that: The dosage ratio of the silane coupling agent solution and the pretreated carbon fiber in S2 is 100 mL: 3-5 g.
6. The novel rubber functional composition for producing bicycle tires according to claim 3, characterized in that: The silane coupling agent solution in S2 is prepared by the following steps: anhydrous ethanol and deionized water are mixed in a volume ratio of 9:1 to obtain an ethanol solution, and KH-550 is added to the ethanol solution in a volume ratio of 4 to 5:1, and stirred at room temperature for 1 to 2 hours. After stirring, a silane coupling agent solution is obtained.
7. The novel rubber functional composition for producing bicycle tires according to claim 3, characterized in that: The usage ratio of N,N-dimethylformamide, graphene oxide and silylated carbon fiber described in S3 is 200mL:0.1~0.5g:1g.
8. The novel rubber functional composition for producing bicycle tires according to claim 1, characterized in that: The grade of the carbon black is N330; the activator is zinc oxide.
9. The novel rubber functional composition for producing bicycle tires according to claim 1, characterized in that: The mesh number of the sulfur is 200 meshes.
10. The novel rubber functional composition for producing bicycle tires according to claim 1, characterized in that: The preparation method of the novel rubber functional composition comprises the following steps: S1. Weigh the raw materials oil-extended solution-polymerized butadiene styrene rubber, oil-extended emulsion-polymerized butadiene styrene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant, activator, carbon black, aromatic oil, sulfur and accelerator according to mass parts and set aside; S2, the oil-extended solution-polymerized styrene-butadiene rubber, the oil-extended emulsion-polymerized styrene-butadiene rubber, natural rubber, butadiene rubber, white carbon black, uniform resin, anti-slip resin, antioxidant and activator are mixed and put into an internal mixer for mixing, the speed of the internal mixer is set to 35-50r / min, the mixing time is 15-50s, and after the mixing is completed, a primary mixed material is obtained; S3, after the internal mixer is lifted, the raw material modified carbon fiber, carbon black and 70% to 80% of the total mass of aromatic oil are added to the primary mixed material, and the speed is set to 20 to 45 r / min, and the mixed material is mixed until the temperature reaches 100 to 125°C to obtain a secondary mixed material, and then the plug is lifted, and the remaining aromatic oil is added to the secondary mixed material, and the speed is set to 10 to 25 r / min, and the mixed material is mixed until the temperature reaches 135 to 150°C, and the temperature is kept constant for 1 to 2 minutes. After the mixing is completed, the material is unloaded to obtain a masterbatch; S4. Mix the masterbatch, raw sulfur and accelerator and put them into an internal mixer. Set the speed to 15-40 r / min and mix until the temperature reaches 80-100° C. The mixing time is 10-30 s. After the mixing is completed, unload the material and cool it to room temperature to obtain a tread rubber composition.